EFFECT ON TEACHER MOTIVATION SOCIAL COMPETENCE IN STUDENTS LEARNING PROCESS IMPROVEMENT: A STUDY OF DISTRICT SCHOOL KORPRI KARAWANG - Isyanto, Puji; MD Fadli, Uus; Sutisna, Deden (International Journal of Psychosocial Rehabilitation, 2020)
Issues to be studied in this research is about student achievement. The core study focused on factors that affect student achievement, namely the social competence of teachers and student motivation. Accordingly, the subject matter disclosed in this study is how far the influence of social competency of teachers and students' motivation on student achievement. The study consists of three variables: Social Competence Master (X1), Student Motivation (X2) and Student Achievement (Y). The method used in this research is explanatory survey method. The data collection technique using a questionnaire sheet. This research data processing using Microsoft Excel 2013. And respondents in this study were students of Class XI Department Office Administration in SMK 1 Bandung taken a sample of 60 respondents. Based on the research results, obtained information that (1) the degree of social competence of teachers affect the level of student achievement, (2) the level of student motivation effect on the level of student achievement, (3) social competence teacher and student motivation effect on the level of student achievement.